Compact embedded RF sawtooth waveform generator for particle accelerator applications - Ashish Sharma; Subrat Kar; Bhuban Kumar Sahu (AIP Advances)
A compact, wideband, completely reconfigurable, and digitally controlled embedded instrument has been designed to generate a sawtooth waveform in the radio frequency regime. This instrument drives an RF structure called a Multi-Harmonic Buncher in a particle accelerator. Its main application is to time-bunch a DC or continuous ion beam for nuclear physics experiments from a particle accelerator, such as an RF linear accelerator, to boost the beam energy. This paper elaborates on the construction of this instrument, including the design and implementation of multiple feedback controls and complex signal processing algorithms to generate a stable sawtooth waveform. The entire design is space and resource-optimized to be hosted on a single system-on-chip field programmable gate array board, which helped reduce the development effort. A TCP/IP-based server–client application has been developed and deployed on the instrument for easy remote operation and reconfiguration of various parameters. Many hardware complexities are handled by the firmware and control software, which provides additional design flexibility over the previous digital designs. While the system can be configured to generate a sawtooth waveform for any frequency in the range of 1–50 MHz, an example application of a 12.125 MHz sawtooth waveform has been presented in detail. This instrument will be tested with the Multi-Harmonic Buncher of the Pelletron and High-Current Injector accelerators of IUAC, New Delhi.